Multiple Shoot Formation in Eggplant (Solanum melongena L.) - Sarker, RH; Yesmin, Sabina; Hoque, MI (Plant Tissue Culture and Biotechnology, 2008)
Among the in vitro derived different explants such as cotyledonary leaf, hypocotyl, shoot tip and root of two local varieties, namely Singhnath and Kazla (BARI Begun-4) of eggplant (Solanum melongena L.) cotyledonary leaf was found to be the best for multiple shoot regeneration. High frequency direct organo-genesis of shoots was achieved from cotyledonary leaf in MS supplemented with 1.0 mg/l BAP and 1.0 mg/l Kn. Anatomical studies using freezing microtome supported the formation of shoots through organogenesis. Proliferation and elongation of such shoots were obtained in hormone free MS. Moreover, the regenerated shoots produced healthy roots when they were cultured on MS without hormonal supplements. Following the formation of roots the in vitro raised plantlets were successfully established in soil. Viable seeds were obtained from the in vitro raised mature plants. Key words: Regeneration, Multiple shoot, Eggplant DOI = 10.3329/ptcb.v16i1.1106 Plant Tissue Cult. & Biotech. 16(1): 53-61, 2006 (June)